Which skin preparation technique is most effective to minimise bacterial contamination?. (2nd April 2019) - Reynolds, Helen; Nichols, Abigail
Abstract : Background: The risk of surgical site infections (SSI) can be addressed by removing organic matter which contains transient and resident flora from the patient's skin prior to surgical incision. Using correct techniques when applying skin preparation solution can significantly reduce bacterial load. Historically the circular technique has been used within veterinary practice for skin preparation prior to surgery; however there has been a recent promotion within the veterinary industry using the back-and-forth technique which has historically been used in human medicine. Aim: The move towards evidence-based medicine suggested testing both skin preparation techniques to determine if either technique was more effective than the other at reducing bacterial load. Method: Five felines undergoing flank ovariohysterectomy surgery were randomly selected for each skin preparation technique with a total sample size of ten felines. Samples of bacterial load were taken before and after the skin was prepared using each technique and cultured in sealed agar plates at a temperature of 38.5°C for 48 hours. Bacterial colonies were then counted and compared pre and post skin preparation. Statistical analysis was performed using 'Minitab'. Results: There was no statistically significant difference between either skin preparation technique at reducing the number of colony forming units (Mann-Whitney U test: W=27.0, N=5, p =1.000). Conclusion: The limited sample size indicated that either technique was as beneficial as the other at preparing the skin for surgery, giving the veterinary nurse confidence in choosing either technique for skin preparation for flank ovariohysterectomy.